Elongational flow induced ordering in surfactant micelles and mesophases. - Penfold, J; Staples, E; Tucker, I; Carroll, P; Clayton, I; Cowan, J; Lawton, G; Amin, S; Ferrante, A; Ruddock, N (2006)
We have used small angle neutron scattering, SANS, to investigate the elongational flow induced ordering in surfactant micelles and mesophases. Spatially resolved SANS measurements have been used to determine the distribution of orientational ordering over the flow velocity pattern in an elongational flow cell, and comparison with the effects of shear flow are made. Two different surfactant systems have been studied, the charged wormlike mixed micelles of hexaethylene monododecyl ether, C16E6/hexadecyl trimethylammonium bromide, C16TAB (3% C16E(6)/5 mol% C16TAB), and the Lalpha lamellar phase of C16E6 (50.6 wt% C16E6 at 55 degrees C), and a substantially different response is observed. The orientational distribution of the Lalpha lamellar phase of C16E6 reflects the flow velocity pattern distribution within the cell, whereas for the wormlike mixed micelles of C16E6/C16TAB this is not the case, and this is associated with the shear thinning behavior of that system.